Pengaruh Motivasi Intrinsik, Budaya Organisasi, dan Pertukaran Pemimpin-Anggota terhadap Kinerja Pegawai (The Influence of Intrinsic Motivation, Organizational Culture, and Leader-member exchange on Employee Performance) - Rikmaratri, Kintan Yuliyan; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (STIE Malangkucecwara, 2025)
This study aims to determine and analyze the effects of intrinsic motivation, organizational culture, and leader-member exchange on employee performance at the Education, Youth, and Sports Office of Bantul Regency. A quantitative approach was employed, collecting primary data through questionnaires administered to 72 respondents. Data processing was conducted using SPSS version 26 to analyze the relationships between variables. The analysis results indicate that intrinsic motivation does not have a significant positive contribution to employee performance. Conversely, organizational culture and leader-member exchange were found to have a significant positive impact on employee performance. These findings emphasize the importance of fostering a positive organizational culture and strong leader-member relationships to enhance employee performance within the organization.